2015
DOI: 10.1007/s10915-015-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Further Results on Guderley Mach Reflection and the Triple Point Paradox

Abstract: Recent numerical solutions and shock tube experiments have shown the existence of a complex reflection pattern, known as Guderley Mach reflection, which provides a resolution of the von Neumann paradox of weak shock reflection. In this pattern, there is a sequence of tiny supersonic patches, reflected shocks and expansion waves behind the triple point, with a discontinuous transition from supersonic to subsonic flow across a shock at the rear of each supersonic patch. In some experiments, however, and in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Numerical solutions also support different models, depending on the approach used in the computations. The inviscid computations [18,19,20] support the Guderley model; however, the viscous numerical [21,22] and analytical [23] solutions do not show any four-wave configurations, supporting the Sternberg model. These viscous effects caused interest to shock reflection in viscous flows at higher Mach numbers [24,25].…”
Section: Introductionmentioning
confidence: 92%
“…Numerical solutions also support different models, depending on the approach used in the computations. The inviscid computations [18,19,20] support the Guderley model; however, the viscous numerical [21,22] and analytical [23] solutions do not show any four-wave configurations, supporting the Sternberg model. These viscous effects caused interest to shock reflection in viscous flows at higher Mach numbers [24,25].…”
Section: Introductionmentioning
confidence: 92%
“…The first confirmation of this model was obtained only half a century later by solving the Euler equations numerically (Vasilev & Kraiko 1999). Further investigations (Hunter & Brio 2000;Tesdall & Hunter 2002;Hunter & Tesdall 2004;Tesdall, Sanders & Keyfitz 2007, 2008Defina, Susin & Viero 2008a;Defina, Viero & Susin 2008b;Vasilev & Olhovskiy 2009;Tesdall, Sanders & Popivanov 2015;Vasil'ev 2016) showed that, depending on problem parameters, configurations formed due to interaction of weak shock waves can have even more complicated structures and contain additional elements of small size. The experiments by Skews & Ashworth (2005) and Skews, Li & Paton (2009) performed in a large shock tube revealed the existence of a configuration similar to that predicted by Guderley and observed in the inviscid studies mentioned above.…”
Section: Introductionmentioning
confidence: 99%